Analisis Faktor Penyebab Kesulitan Belajar Matematika Pada Siswa - Erwin Syahputra, Rustam (Mulya Literasi Publishing, 2022)
Mathematics is learning that is needed in everyday life to think critically with the ability to think logically, analytically, systematically, innovatively, and estimate the results of arithmetic operations. And many students consider math a difficult learning. This study aims to analyze the factors that cause math learning difficulties and what efforts teachers make to deal with math learning difficulties. This is a qualitative research with the subjects of 26 students who indicated math learning difficulties. The conclusion of this research is that the factors that cause math learning difficulties internal factors include maturity/growth, intelligence, training, motivation and personal factors. While external factors include family factors, teacher teaching methods, learning media and the school environment. Efforts made by teachers to overcome mathematics learning difficulties are providing learning motivation, providing a variety of teaching methods, providing sufficient and repeated practice, using teaching aids and providing remedial programs.